Toward a generalized computational workflow for exploiting transient pockets as new targets for small molecule stabilizers: Application to the homogentisate 1, 2-dioxygenase mutants at the base of rare disease Alkaptonuria. (October 2017) - Bernini, Andrea; Galderisi, Silvia; Spiga, Ottavia; Bernardini, Giulia; Niccolai, Neri; Manetti, Fabrizio; Santucci, Annalisa
Graphical abstract: Highlights: A new approach to the treatment of Alkaptonuria is proposed by use of Pharmacological Chaperones (PCs). Transient pockets at the surface of mutated enzyme are exploited as targets for PC. A workflow employing ready-to-use tools is proposed. Abstract: Alkaptonuria (AKU) is an inborn error of metabolism where mutation of homogentisate 1, 2-dioxygenase (HGD) gene leads to a deleterious or misfolded product with subsequent loss of enzymatic degradation of homogentisic acid (HGA) whose accumulation in tissues causes ochronosis and degeneration. There is no licensed therapy for AKU. Many missense mutations have been individuated as responsible for quaternary structure disruption of the native hexameric HGD. A new approach to the treatment of AKU is here proposed aiming to totally or partially rescue enzyme activity by targeting of HGD with pharmacological chaperones, i.e. small molecules helping structural stability. Co-factor pockets from oligomeric proteins have already been successfully exploited as targets for such a strategy, but no similar sites are present at HGD surface; hence, transient pockets are here proposed as a target for pharmacological chaperones. Transient pockets are detected along the molecular dynamics trajectory of the protein and filtered down to a set of suitable sites for structural stabilization by mean of biochemical and pharmacological criteria. The result is a computational workflow relevant to other inborn errors of metabolism requiring rescue of oligomeric, misfolded enzymes.